(untitled) (Journal of actual problems of jurisprudence, 2019)
The paper discusses some issues of developing a legal framework for the further improvement of the infrastructure market for payment cards, and to create in Kazakhstan ‘s national operator for unified management and implementation of the acquiring network processing operations on payment cards . Author analyzes the concept of the project to the project of the Law «On amendments and additions to some legislative acts of Kazakhstan on improvement of legislation in the Republic of Kazakhstan to make payments and transfer money». Key words: acquiring infrastructure, payment technologies, processing transactions on payment cards, banking.